IMPLEMENTASI KEBIJAKAN PENGARUSUTAMAAN GENDER DALAM PROGRAM RURAL INFRASTRUCTURE SUPPORT – PNPM MANDIRI DI KECAMATAN PAGAR GUNUNG KABUPATEN LAHAT TAHUN 2014 - Een Endasari; Endasari, Een (Jurnal Pemerintahan dan Politik, 2019)
This research is "Gender Mainstreaming Policy in Rural Infrastructure Support to the PNPM (National Programme for Community Empowerment) Mandiri program implementation. The focuses of this study is the performance achievement and impact of the gender mainstreaming implementation through the implementation of the RIS-PNPM program in accordance with the objectives of gender mainstreaming policy, namely: access, control, participation and benefit.Keywords : Policy, Gender mainstreaming, Implementation